Understanding the Dimensions of Entrepreneurial Marketing for Startups in Developing Economies - Deepta, Aqib Wassy (2020)
The concept of Entrepreneurial Marketing emerged to bridge the gap between entrepreneurship and marketing, and this concept has developed rapidly in the last decade. Although several studies have explored the dimensions of entrepreneurial marketing, yet these studies rarely considered startups. Since startups operate with limited resources and encounter greater challenges as a new entrant in the market, they tend to be opportunity-driven and innovative, which are fundamentals of the entrepreneurial marketing concept. Besides, it has been observed that startups operating in a developing economy face challenges that might not be encountered in a developed economy. Moreover, it has been noticed that a very limited number of studies are based on the developing economy. Therefore, this research explores the dimensions of entrepreneurial marketing that influence startups in a developing economy. Furthermore, it explains how the dimensions: proactive orientation, opportunity-driven, customer-intensity, innovation-focused, risk management, value creation, and strategic legitimacy influence startups which are operating in a developing country. Among these, the dimension of strategic legitimacy is a new addition that has not been considered in the previously established models. This research can prove to be valuable for both academic purposes and entrepreneurs. Based on the outcomes, this research suggests the priorities for future research as well.